Doxorubicin conjugated to d-α-tocopheryl polyethylene glycol 1000 succinate (TPGS): Conjugation chemistry, characterization, in vitro and in vivo evaluation - Cao, N. (2014)
10.1016/j.biomaterials.2008.05.016